Technological tools and competence investigates the educational institution 1222 hussars of Junín de Ate (Alpha Centauri, 2022)
The research set out to demonstrate the effects of the application of technological tools in the competition inquires through scientific methods to build knowledge in students of the fourth grade of primary school. The research approach was quantitative, the general methodology corresponded to the scientific method and the observation and experimental method in the specific one. The quasi-experimental design with two non-equivalent groups was applied. The type of research was applied, the study sample was made up of 70 fourth grade students. To measure the variables, psychometry was used; constituted in pre-test and post-test, the independent variable effects of the technological tools was manipulated in the dependent variable competence inquires. The international researchers Sánchez (2016), Cuevas et al. (2015), Granda et al. (2019) and the Peruvians Tarrillo (2018), Martínez and Poma (2018). It was shown that technological tools have positively influenced the development of the research competition through scientific methods to build knowledge in the fourth grade students of the Educational Institution 1222 Húsares de Junín de Ate in 2021.